Material characterization of high strength sound-deadening sheets and its application on a square cup drawing simulation. (November 2019) - Park, Hyeonil; Kim, Se-Jong; Lee, Jinwoo; Kim, Daeyong
Abstract: In this study, the mechanical properties of a high strength sound-deadening sheet (SDS) in the stretch deformation mode was characterized, and it successfully apply to the formability prediction of the square cup drawing tests. The high strength SDS was fabricated with dual phase (DP) 590 steel sheets as outer skins and polymeric adhesive layer as a core by a roll bonding process. Uniaxial and biaxial mechanical characteristics were evaluated by the uniaxial tension tests and the in-plane biaxial tension tests, respectively, while the forming limit was investigated by the punched dome tests. Then, based on the experimental data, the mechanical properties of SDS was characterized, viz., hardening curve, yield function and forming limit curve. Square cup drawing was carried out using the SDS, and its deformation and failure behaviour were successfully predicted via the finite element simulation performed by inputting characterized mechanical properties.